Burning Characteristics of Ammonium-Nitrate-Based Composite Propellants with a Hydroxyl-Terminated Polybutadiene/Polytetrahydrofuran Blend Binder - Makoto Kohga; Tomoki Naya; Kayoko Okamoto (International Journal of Aerospace Engineering)
Ammonium-nitrate-(AN-) based composite propellants prepared with a hydroxyl-terminated polybutadiene (HTPB)/polytetrahydrofuran (PTHF) blend binder have unique thermal decomposition characteristics. In this study, the burning characteristics of AN/HTPB/PTHF propellants are investigated. The specific impulse and adiabatic flame temperature of an AN-based propellant theoretically increases with an increase in the proportion of PTHF in the HTPB/PTHF blend. With an AN/HTPB propellant, a solid residue is left on the burning surface of the propellant, and the shape of this residue is similar to that of the propellant. On the other hand, an AN/HTPB/PTHF propellant does not leave a solid residue. The burning rates of the AN/HTPB/PTHF propellant are not markedly different from those of the AN/HTPB propellant because some of the liquefied HTPB/PTHF binder cover the burning surface and impede decomposition and combustion. The burning rates of an AN/HTPB/PTHF propellant with a burning catalyst are higher than those of an AN/HTPB propellant supplemented with a catalyst. The beneficial effect of the blend binder on the burning characteristics is clarified upon the addition of a catalyst. The catalyst suppresses the negative influence of the liquefied binder that covers the burning surface. Thus, HTPB/PTHF blend binders are useful in improving the performance of AN-based propellants.